2014
DOI: 10.2147/ijwh.s63167
|View full text |Cite
|
Sign up to set email alerts
|

Role of uterine forces in intrauterine device embedment, perforation, and expulsion

Abstract: BackgroundThe purpose of this study was to examine factors that could help reduce primary perforation during insertion of a framed intrauterine device (IUD) and to determine factors that contribute in generating enough uterine muscle force to cause embedment and secondary perforation of an IUD. The objective was also to evaluate the main underlying mechanism of IUD expulsion.MethodsWe compared known IUD insertion forces for “framed” devices with known perforation forces in vitro (hysterectomy specimens) and kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 32 publications
0
81
0
3
Order By: Relevance
“…In this case the likelihood of problems (e.g, expulsion, embedment) in any group, nulliparous or multiparous is drastically reduced [26]. If the transverse arm of the IUD is too long as in Figure 4A-C, then the IUD will either be expelled due to symmetrical expulsive forces or the anchor becomes pathological, causing embedment and bleeding due to asymmetrical uterine forces acting on the IUD [27]. In the latter case, the uterus may not be capable of expelling the IUD.…”
Section: Discussionmentioning
confidence: 99%
“…In this case the likelihood of problems (e.g, expulsion, embedment) in any group, nulliparous or multiparous is drastically reduced [26]. If the transverse arm of the IUD is too long as in Figure 4A-C, then the IUD will either be expelled due to symmetrical expulsive forces or the anchor becomes pathological, causing embedment and bleeding due to asymmetrical uterine forces acting on the IUD [27]. In the latter case, the uterus may not be capable of expelling the IUD.…”
Section: Discussionmentioning
confidence: 99%
“…If the IUD is not fully expelled, embedment and/or secondary perforation of the IUD may occur. The imbalance between the size of the IUD and that of the uterine cavity can result in the production of asymmetrical uterine forces, which can increase patient discomfort especially while menstruating [16]. Hubacher's review of copper IUDs revealed that nulliparous women experience higher rates of total expulsion and removals for bleeding and/or pain compared with parous women [17].…”
Section: Is There An Association Of Malposition and Subsequent Expulsmentioning
confidence: 99%
“…Incompatibility between the IUD and the endometrial cavity will provoke uterine contraction in an attempt to expel the IUD. The impact of uterine forces can be significant if the transverse arm of the IUD/IUD is significantly greater than the fundal transverse diameter [16]. These forces can compress, distort, displace, and expel the IUD, particularly if the IUD is not capable of adaptive changes [30].…”
Section: How To Avoid Iud Malposition and Displacementmentioning
confidence: 99%
“…The attachment to the fundus of the uterus minimizes the risk of expulsion [22,23]. Long term comfort, especially for those women (e.g., nulliparous and adolescent women) with a small or distorted uterine cavity, and for women who have experienced problems with framed IUDs can be achieved with a frameless IUD ( Figure 9) [19,24].…”
Section: The Frameless Copper Iud (Gynefix)mentioning
confidence: 99%